1995
DOI: 10.1007/bf00201416
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the generation of averaged modified trajectories

Abstract: Abstract. In this work we have studied what mechanisms might possibly underlie arm trajectory modification when reaching toward visual targets. The double-step target displacement paradigm was used with inter-stimulus intervals (ISis) in the range of 10-300 ms. For short ISis, a high percentage of the movements were found to be initially directed in between the first and second target locations (averaged trajectories). The initial direction of motion was found to depend on the target configuration, and on D: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 28 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…In addition, mean duration of paused movement was significantly shorter in Experiment 1 than Experiment 2 (117 vs. 156 ms; χ 2 (1) = 5.57, p = 0.018). Although the proportion of paused movements was similar with both scene conditions in both experiments, the duration of the pause was significantly different between the scene that was matched to head motion (120 ms) and the rolling scene (190 ms) in Experiment 2 (χ 2 (1) = 15.8, p < 0.0001). Furthermore, the 3D hand path was consistently curved for both single-and double-step conditions, irrespective of target position and scene condition.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, mean duration of paused movement was significantly shorter in Experiment 1 than Experiment 2 (117 vs. 156 ms; χ 2 (1) = 5.57, p = 0.018). Although the proportion of paused movements was similar with both scene conditions in both experiments, the duration of the pause was significantly different between the scene that was matched to head motion (120 ms) and the rolling scene (190 ms) in Experiment 2 (χ 2 (1) = 15.8, p < 0.0001). Furthermore, the 3D hand path was consistently curved for both single-and double-step conditions, irrespective of target position and scene condition.…”
Section: Resultsmentioning
confidence: 80%
“…Studies have shown that both young and elderly healthy subjects are able to amend their ongoing movements in response to target displacement during a "double-step" paradigm which changes the spatial goal of the movement by unexpectedly changing the location of a visual target [1][2][3][4]. However, these movements have only been tested in stationary visual environments.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy would be in line with the hypothesis of an intermittent controller that sequentially initiates discrete movement primitives (Fishbach et al, 2005; Loram et al, 2010; Squeri et al, 2010; Karniel, 2013). Submovements might be combined in time succession (Soechting and Terzuolo, 1987; Meyer et al, 1988), or based on the vectorial summation of overlapping preplanned trajectories (Flash and Henis, 1991; Henis and Flash, 1995; Novak et al, 2003; Roitman et al, 2004; Pasalar et al, 2005). In this manuscript we have exemplified the former approach; the analysis of the latter by means of DRD is non-trivial, and it is therefore left for future work.…”
Section: Discussionmentioning
confidence: 99%
“…This set-up provided the flexibility needed to conduct home-based measurements as no advanced 3D kinematic system was needed. The 2D registration has been shown to be valid and reliable in earlier studies (Henis & Flash, 1995;van Sonderen, Gielen, & Denier van der Gon, 1989). We chose to use the finger and not a pen or stylus as the touchpoint on the screen because handwriting problems are well known in children with DCD (Prunty, Barnett, Wilmut, & Plumb, 2013;Rosenblum & Livneh-Zirinski, 2008).…”
mentioning
confidence: 85%